Prognostic value of rise in neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in predicting the mortality in paediatric intensive care - Mathews, Siby; Rajan, Aswathy; Soans, Santosh T. (International Journal of Contemporary Pediatrics, 2019)
Background: When the body is stressed in diverse pathological conditions, it responds by mounting an inflammatory response. Predictive biomarkers reflecting the response may serve as guide to management. Neutrophil to Lymphocyte Ratio and Platelet to Lymphocyte Ratio has been frequently used in adult patients as an indicator for mortality. However, no study has looked into their use within pediatric population. The objective of the study is to assess the prognostic value of rise in NLR and PLR in pediatric intensive care as markers of mortality. Methods: A retrospective study based on 3 year data from HIMS and G-HEALTH data systems of AJ Institute of Medical Science, of all patients admitted to PICU after excluding those in whom all the study parameters were not retrievable, were postoperative patients and/or stay was less than 5 days. NLR and PLR ratios were determined and compared to PELOD 2 using SPSS version 17.0. Results: The demographic data was matched. PELOD 2 (>20) predicted mortality in 72.2% of the patients, while NLR increase predicted in 61.1% and PLR increase in 77.8%. A decreasing trend in NLR and PLR were both closely related to better survival. Among the 3, Rise in PLR had higher sensitivity, specificity, PPV, NPV, and overall accuracy of 72.73% (p <0.001) to predict mortality. Conclusions: The study gives an insight into the fact that simple and inexpensive markers such as rise in NLR and PLR helps in predicting the mortality in the pediatric intensive care which is comparable to PELOD 2 score.